Meridional Heat and Salinity Transports and the Surface Freshwater Exchange Derived from the OSNAP (Overturning in the Subpolar North Atlantic Program) Array between August 2014 and May 2018 - Li, Feili; Lozier, M. Susan; Bacon, S.; Cunningham, S.A.; Bower, A.; de Jong, M.F.; DeYoung, B.; Fraser, N.; Fried, N.; Han, G.; Holiday, N.P.; Holte, J.; et al. (Georgia Institute of Technology, 2021)
Data from the full OSNAP array for the first 4 years between 2014 and 2018 have been used to produce the 30-day mean meridional heat (MHT) and salinity transports (MST), and the derived surface freshwater (FW) exchange time series. Related article: Observation-based estimates of heat and freshwater exchanges from the subtropical North Atlantic to the Arctic An international effort, Overturning in the Subpolar North Atlantic Program (OSNAP), is a partnership among oceanographers from the US, UK, Germany, the Netherlands, Canada and China whose goal is to measure and understand what drives the subpolar overturning circulation and its associated property exchanges. OSNAP is consisted of more than 53 moorings that stretch from Labrador to Greenland to Scotland, providing a continuous record of the full water column, trans-basin velocity, temperature and salinity in the subpolar North Atlantic. Data from the full OSNAP array for the first 4 years between 2014 and 2018 have been used to produce the 30-day mean meridional heat (MHT) and salinity transports (MST), and the derived surface freshwater (FW) exchange time series. National Science Foundation Award Number 1948335